2011
DOI: 10.1007/s12291-011-0164-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of C-Reactive Protein and Myocardial Infarction in the Indian Population

Abstract: To analyse the association of high sensitivity C-reactive (hsCRP) protein levels and -717A/G single nucleotide polymorphism of CRP with acute myocardial infarction (AMI) in the Indian population. Study population included 100 MI cases wherein 32 patients had experienced previous MI (MI-Group-1), 68 MI cases were recruited at presentation (MI-Group-2) and equal number of age and gender matched healthy individuals. hsCRP levels were determined by ELISA and genotyping of -717A/G was carried out by polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We finally were left with 16 studies. 14 , 15 , 18 20 , 28 – 38 As shown in Table 1 , 9 studies from the USA, Italy, Croatia, Germany, Iran, Egypt, or India were categorized as Caucasians and the remainders consisting of 7 Asian studies were all conducted in Chinese subjects. There were 14 case–control studies for +942G C, 5 for −717A G, and 3 for +1444C T. The Asian studies had a relatively smaller sample size compared with the Caucasian studies.…”
Section: Resultsmentioning
confidence: 99%
“…We finally were left with 16 studies. 14 , 15 , 18 20 , 28 – 38 As shown in Table 1 , 9 studies from the USA, Italy, Croatia, Germany, Iran, Egypt, or India were categorized as Caucasians and the remainders consisting of 7 Asian studies were all conducted in Chinese subjects. There were 14 case–control studies for +942G C, 5 for −717A G, and 3 for +1444C T. The Asian studies had a relatively smaller sample size compared with the Caucasian studies.…”
Section: Resultsmentioning
confidence: 99%
“…The HDL-C particle is believed to be anti-atherogenic and antagonized pathways of inflammation, thrombosis, and oxidation. [9][10][11][12][13] Unlike to male with myocardial infarction the mean serum levels of LDL-C were significantly higher (P <0.05) in the female with myocardial infarction compared to the control. Studies have shown that the levels of LDL-C were associated with atherosclerosis.…”
Section: Serum Low-density Lipoprotein (Ldl-c)mentioning
confidence: 99%
“…C-reactive protein (CRP), a marker of systemic inflammation and synthesized in liver, has been received considering attention in aging mediated inflammatory disorders such as CVD, osteoarthritis and cancer etc. [3][4][5]. Previous studies have demonstrated an association between age related disorders and inflammation as measured by plasma C-reactive protein Original Research Article [6,7].…”
Section: Introductionmentioning
confidence: 99%